High Endothelial Venules and Other Blood Vessels: Critical Regulators of Lymphoid Organ Development and Function - Ager, Ann (Frontiers in Immunology, 2017)
The blood vasculature regulates both the development and function of secondary lymphoid organs by providing a portal for entry of haemopoietic cells. During the development of lymphoid organs in the embryo, blood vessels deliver lymphoid tissue inducer cells which initiate and sustain the development of lymphoid tissues. In adults, the blood vessels are structurally distinct from those in other organs due to the requirement for high levels of lymphocyte recruitment under non-inflammatory conditions. In lymph nodes and Peyer’s patches, high endothelial venules (HEV) especially adapted for lymphocyte trafficking form a spatially organised network of blood vessels which controls the both the type of lymphocyte and the site of entry into lymphoid tissues. Uniquely, HEV express vascular addressins which regulate lymphocyte entry into lymphoid organs and are, therefore, critical to the function of lymphoid organs. Recent studies have demonstrated important roles for CD11c+ dendritic cells in the induction, as well as the maintenance, of vascular addressin expression and, therefore, the function of HEV. Tertiary lymphoid organs (TLOs) are HEV containing, lymph node-like structures that develop inside organised tissues undergoing chronic immune-mediated inflammation. In autoimmune lesions, the development of TLOs is thought to exacerbate disease. In cancerous tissues, the development of HEV and TLOs is associated with improved patient outcomes in several cancers. Therefore, it is important to understand what drives the development of HEV and TLOs and how these structures contribute to pathology. In several human diseases and experimental animal models of chronic inflammation, there are some similarities between the development and function of HEVs in LN and TLOs. This review will summarise current knowledge of how haemopoietic cells with lymphoid tissue-inducing, HEV-inducing and HEV-maintaining properties are recruited from the bloodstream to induce the development and control the function of lymphoid organs.